Pengaruh Debt Asset Ratio (DAR) dan Debt Equity Ratio (DER) Terhadap Return on Asset (ROA) pada Perusahaan Jasa Telekomunikasi yang Terdaftar di Bursa Efek Indonesia periode 2018 – 2021 - Muh Fuad Randy; Abdul Sumarlin; Astuty Hasti (CV ODIS, 2022)
The ratios that can affect the size of a company's ROA value are the Debt Asset Ratio (DAR) and the Debt Equity Ratio (DER). The DAR ratio is the ratio used to measure the ratio between total debt and total assets. While the DER is the ratio between debt and equity in the company's funding and shows the company's own capital ability to fulfill all its obligations. This study aims to determine the effect of Debt Asset Ratio (DAR) and Debt Equity Ratio (DER) on Return on Assets (ROA) in Telecommunication Service Companies Listed on the Indonesia Stock Exchange for the period 2018-2021. The type of research used is an empirical study. The data analysis method used is documentation of secondary data using the DAR, DER, and ROA formulas. The data analysis technique used was multiple linear regression analysis. The results of multiple linear regression testing and classical assumptions obtained from the calculation of the partial t-test Debt Asset Ratio (DAR) (X1) partially (alone) effect on Return on Assets (ROA) or variable (Y) with a sig value of 0.018 < 0.05 , Debt Equity Ratio (DER) (X2) also has a partial effect on Return on Assets (ROA) or variable (Y) with a sig value of 0.029 < 0.05, the calculated F value and the F table obtained is an f arithmetic value of 3.691 < 3.74 f table value, the independent variable (X) simultaneously has no effect on the dependent variable (Y), the percentage value of the X and Y variables partially and simultaneously gives an effect of 36.2%. as input for telecommunications service companies PT Indosat Tbk, PT Smarfren Telecom, PT Telkom Indonesia Tbk and PT XL Axiata Tbk pay attention to the achievement of net profit to be further improved and extra attention is needed and if possible more effective and efficient in managing its debts and every year maintain the stability of its DAR and DER.